Laser Scanning Tomography in the EPIC-Norfolk Eye Study: Principal Components and Associations - Khawaja, Anthony P. (The Association for Research in Vision and Ophthalmology, 2013)
PURPOSE. To describe Heidelberg Retina Tomograph (HRT) measures, their principal components, and their associations in a British population. METHODS. The European Prospective Investigation of Cancer (EPIC)-Norfolk Eye Study is nested within a multicenter cohort study. Measurements were taken with the HRT-2 and the software subsequently updated to yield HRT-3 parameters. Principal components analysis (PCA) was used to identify distinct components of the HRT variables. Generalized estimating equation models were used to examine associations of these components with age, sex, height, body mass index (BMI), blood pressure, social class, education, alcohol intake, smoking status, axial length, IOP, and lens status. RESULTS. Complete data were available from 10,859 eyes of 6430 participants with a mean age of 68 years. Principal components analysis identified three components with an eigenvalue greater than 1, explaining 79.9% of the variance of all the HRT measures. These were named cup, retinal nerve fiber layer (RNFL), and rim based on the factor loadings they were most correlated with. Older age was significantly associated with a greater cup (P = 0.003), smaller RNFL (P < 0.001), and smaller rim (P < 0.001). Female sex (P = 0.001), higher education (P < 0.001), and shorter axial length (P < 0.001) were associated with a greater RNFL. Lower BMI and higher IOP were associated with a greater cup (both, P < 0.001) and a smaller rim (BMI, P = 0.001; IOP, P < 0.001). CONCLUSIONS. Heidelberg Retina Tomograph measures in this cohort were largely explained by three principal components related to optic disc cup, RNFL, and rim. Associations with cup and rim were distinct to associations with RNFL, suggesting different underlying determinants.